Nutrition value and viscosity of polymeric enteral nutrition products based on purple sweet potato flour with variation of maltodextrin levels - Rauf, Rusdin; Utami, Anggraeni (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2020)
Background: One obstacle in commercial enteral food formulation is the adjustment between nutritional value and rheological characteristics of the product.Objectives: To evaluate the nutritional value and viscosity of polymeric enteral nutrition (PEN) products made from purple sweet potato flour with variations in the level of maltodextrin as a stabilizer.Methods: The completely randomized design was used with four variations of maltodextrin, which was 2.5%, 5%, 7.5%, and 10%. The research was carried out by making purple sweet potato flour, then its proximate composition was measured as a basis for formulating a PEN product that was 200 kcal/200mL, with 60% carbohydrates (120 kcal / 200 mL), 15% protein (30 kcal), and 25% fat (50 kcal). The proximate composition and calorie value of the PEN products were tested. The PEN products were added hot water at a temperature of 90ËšC; then, the viscosity was measured at room temperature. The viscosity of two types of commercial enteral nutrition products was measured as a reference.Results: The results showed that there was an effect of maltodextrin level on moisture, fat, and protein contents of PEN products, but there was no effect on calorie values. The viscosity of the PEN products displayed that the higher the maltodextrin level, the higher the viscosity of the product. The viscosity of the PEN products in accordance with the commercial enteral products was the treatment of maltodextrin 5% and 7.5%.Conclusion: There is an effect of maltodextrin as a stabilizer on the nutritional value and viscosity of PEN products based on purple sweet potato flour.